MODEL BIMBINGAN TEMAN SEBAYA UNTUK MENINGKATKAN PERILAKU PROSOSIAL SISWA DI SMA NEGERI 6 MADIUN - Rahayu, Dwi Sri (Widya Warta, 2016)
The purpose of this study is to (1) find out the objective conditions associated with the peer guidance in SMA Negeri 6 Madiun, (2) knowing the behavior of prososial students in SMA Negeri 6 Madiun, (3) produce peer mentoring model to improve the behavior of prosocial students in SMA Negeri 6 Madiun, (4) determine the effectiveness of peer mentoring model to improve the behavior of prosocial students in SMA Negeri 6 Madiun. This research is research reseach and development (RnD) and the steps: (1) a preliminary study, (2) formulating model hipotetic, (3) test the feasibility of a model hipotetic, (4) the improvement of model hipotetic, (5) a limited trial, (6) the end result product. This research resulted in a peer guidance model to improve the behavior of prosocial students in SMA Negeri 6 Madiun. Based on the results of the field test, peer guidance model proved effective for increasing behaviors prosocial students. This is demonstrated by student behavior prosocial rate change before treatment (pretes) and after (postes) amounted to 146 points. The results of the test of wilcoxon statistics also show the value of wilcoxon-3.625 < 0.05 means that Ho is rejected and Ha is accepted.